2021
DOI: 10.1186/s12981-020-00328-6
|View full text |Cite
|
Sign up to set email alerts
|

Trends and factors associated with modification or discontinuation of the initial antiretroviral regimen during the first year of treatment in the Turkish HIV-TR Cohort, 2011–2017

Abstract: Background There is limited evidence on the modification or stopping of antiretroviral therapy (ART) regimens, including novel antiretroviral drugs. The aim of this study was to evaluate the discontinuation of first ART before and after the availability of better tolerated and less complex regimens by comparing the frequency, reasons and associations with patient characteristics. Methods A total of 3019 ART-naive patients registered in the HIV-TR c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 27 publications
0
4
0
1
Order By: Relevance
“…Many studies have reported toxicity/intolerance as a major driver of cART modi cation globally (8,11,(19)(20)(21). In Ethiopia, pooled data from 17 studies identi ed intolerance/toxicity as the major cause of treatment modi cation (8% (95% CI: 46, 69%; Range: 14.4-88.5%) (11).…”
Section: Resultsmentioning
confidence: 99%
“…Many studies have reported toxicity/intolerance as a major driver of cART modi cation globally (8,11,(19)(20)(21). In Ethiopia, pooled data from 17 studies identi ed intolerance/toxicity as the major cause of treatment modi cation (8% (95% CI: 46, 69%; Range: 14.4-88.5%) (11).…”
Section: Resultsmentioning
confidence: 99%
“…The recommendation was informed by high value evidence connecting d4T to lactic acidosis (LA), peripheral neuropathy, lipodystrophy, and AEs associated with mitochondrial toxicity 18 . In prior years, patients in these settings were retained on d4T (despite active www.nature.com/scientificreports/ Many studies have reported toxicity/intolerance as a major driver of cART modification globally 8,11,[19][20][21] . In Ethiopia, pooled data from 17 studies identified intolerance/toxicity as the major cause of treatment modification (8% (95% CI 46, 69%; Range: 14.4-88.5%) 11 .…”
Section: Discussionmentioning
confidence: 99%
“…En este estudio retrospectivo describimos la evolución de la terapia antirretroviral en los últimos 5 años. Si analizamos estudios previos, como el de Korten et al [ 6 ] donde analizaban los motivos de cambio de TAR de 1ª línea (2011-2017), la interrupción por intolerancia/toxicidad fue la principal causa, mismo resultado que el obtenido en el estudio de SobrinoJiménez C. [ 7 ] durante diciembre del 2014. En ambos estudios el esquema ITIAN más frecuente era el que contenía tenofovir disoproxil en su forma de sal de fumarato (TDF), destacado por su toxicidad renal y ósea, y, a pesar de que estas toxicidades ya venían descritas en las guías, no fue hasta el 2018 cuando la guía geSIDA [ 8 ] menciona en sus recomendaciones de esquemas preferentes el uso únicamente de la forma tenofovir alafenamida (TAF).…”
Section: Discussionunclassified